Health Protection of CT Radiographers During the Outbreak of COVID-19: Application of Automatic Positioning Technology for Relocatable CT in the Fang Cang Hospital - Jiang, Shan; Jiang, Zhongbiao; Luo, Li-Hua; Yu, Kun; Cai, Yeyu; Xie, Xingzhi; Zhao, Wei; Situ, Weijun; Liu, Jun; Chen, Zhu (Frontiers in Medicine, 2021)
To investigate the value of automatic positioning technology in improving the protection of radiographers in the relocatable CT room of a Fang Cang Hospital during the outbreak of coronavirus disease 2019 (COVID-19). The National Emergency Medical Team of our hospital assumed command of Wuchang Fang Cang Hospital and treated confirmed COVID-19 patients with mild symptoms. Relocatable CT was used to examine patients in this hospital. Automatic positioning technology was applied to avoid close contact between medical staff and patients and to protect medical staff more effectively. 700 lung CT scans acquired from 269 patients were completed from February 17 to February 26 of 2020 with automatic positioning technology for relocatable CT in a Fang Cang Hospital. All scans were conducted successfully using automatic positioning technology. All patients entered the scanning room from a separate door. All the position lines were accurate, and all images met the requirement for diagnosis of COVID-19, with satisfied quality. None of our medical staff had any close contact with patients. Automatic positioning technology applied to relocatable CT can minimize the close contact between technologists and patients and effectively improve the protection of medical staff without sacrificing image quality.